Report on China - Heimberger, Heidi,Horvat, Djerdj,Kroll, Henning,Shauchuk, Palina (European Commission, 2020)
The objective of the international country reports is to explore the technology and policy landscape of selected non-European countries. Country performance in advanced technologies is presented based on patent, trade and investment data. The reports provide also a concise and informative review of policies relevant for advanced technology development and deployment. The starting point of this analysis has been sixteen advanced technologies that are a priority for European industrial policy and that enable process, product and service innovation throughout the economy and hence foster industrial modernisation. Advanced technologies are defined as recent or future technologies that are expected to substantially alter the business and social environment and include Advanced Materials, Advanced Manufacturing, Artificial Intelligence, Augmented and Virtual Reality, Big Data, Blockchain, Cloud Technologies, Connectivity, Industrial Biotechnology, the Internet of Things, Micro and Nanoelectronics, Mobility, Nanotechnology, Photonics, Robotics and Security. The full methodology behind the data calculations is available on the ATI website: https://ati.ec.europa.eu. The report is structured as the following: The first section outlines the capacities of China in terms of technology generation (patent applications), followed by an analysis of international competitiveness in technology-based products (export shares) and, eventually, entrepreneurial dynamism (venture capital activities and investments in tech firms). The second section analyses the main policy strategy of China in support of advanced technologies and provides an overview of some of the key policy initiatives and policy measures in the field.
10.2826/474069
Keywords: Graue Literatur; Technischer Fortschritt; Performance-Messung; China; new technology; Brazil; trade policy; investment; company modernisation; advanced materials; artificial intelligence; virtual community; big data; nanotechnology; robotics; blockchain; cloud computing; information security; Internet of Things; biotechnology; report